Sexual violence in the media indirect effects on aggression against women - Malamuth, Neil M.; Briere, John (1986)
We present a model hypothesizing indirect effects of media sexual violence on aggression against women. It suggests that certain cultural factors (including mass media) and individual variables interact to affect some people's thought patterns and other responses that may lead to antisocial behavior, including aggression. Two streams of current research are relevant to the model. The first shows connections between exposure to sexually violent and the development of thought patterns that support violence against women. This second reveals links between such patterns and various forms of antisocial behavior in the laboratory and in naturalistic settings. Suggestions for further research are discussed.